Is private insurance enough to address barriers to accessing dental care? Findings from a Canadian population-based study - Mona Abdelrehim; Sonica Singhal (BMC, 2024)
Abstract Background In Canada, as in many other countries, private dental insurance addresses financial barriers to a great extent thereby facilitating access to dental care. That said, insurance does not guarantee affordability, as there are issues with the quality and level of coverage of insurance plans. As such, individuals facing barriers to dental care experience poorer oral health. Therefore, it is important to examine more keenly the socio-demographic attributes of people with private insurance to particularly identify those, who despite having insurance, face challenges in accessing dental care and experience poorer oral health. Methods This study is a secondary data analysis of the most recent available cycle (2017-18) of the Canadian Community Health Survey (CCHS), a national cross-sectional survey. Univariate analysis was conducted to determine the characteristics of Ontarians with private insurance (n = 17,678 representing 6919,814 Ontarians)-bivariate analysis to explore their financial barriers to dental care, and how they perceive their oral health. Additionally, logistic regressions were conducted to identify relationships between covariates and outcome variables. Results Analysis shows that the majority of those with private insurance do not experience cost barriers to dental care and perceive their oral health as good to excellent. However, specific populations, including those aged 20-39 years, and those earning less than $40,000, despite having private dental insurance, face significantly more cost barriers to access to care compared to their counterparts. Additionally, those with the lowest income (earning less than $20,000 annually) perceived their oral health as "fair to poor" more than those earning more. Adjusted estimates revealed that respondents aged 20-39 were six times more likely to report cost barriers to dental care and ten times more likely to visit the dentist only for emergencies than those aged 12-19. Additionally, those aged 40-59 were two times more likely to report poorer oral health status compared to those aged 12-19. Conclusion Given the upcoming implementation of the Canadian Dental Care Plan, the results of this study can support in identifying vulnerable populations who currently are ineligible for the Plan but can be benefitted from the coverage.